Post-compression of high-energy, sub-picosecond laser pulses. (16th February 2023) - Bleotu, P.-G.; Wheeler, J.; Mironov, S. Yu.; Ginzburg, V.; Masruri, M.; Naziru, A.; Secareanu, R.; Ursescu, D.; Perez, F.; De Sousa, J.; Badarau, D.; Veuillot, E.; et al.
Abstract: The post-compression technique based on self-phase modulation of high-energy pulses leads to an increase in achievable peak power and intensity. Typically, the pulses considered in experiments have been less than 100 fs in duration. Here, the method is applied to the ELFIE laser system at the LULI facility, for a pulse of 7 J energy and an initial measured duration of 350 fs. A 5-mm-thick fused silica window and a 2 mm cyclic-olefin polymer were used as optical nonlinear materials. The 9 cm diameter beam was spectrally broadened to a bandwidth corresponding to 124 fs Fourier-limited pulse duration, and then it was partly post-compressed to 200 fs. After measuring the spatial spectra of the beam fluence, a uniform gain factor of 4 increase in the fluctuations over the studied range of frequencies is observed, due to small-scale self-focusing.